2017
DOI: 10.1111/mec.14184
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput sequencing of transposable element insertions suggests adaptive evolution of the invasive Asian tiger mosquito towards temperate environments

Abstract: Invasive species represent unique opportunities to evaluate the role of local adaptation during colonization of new environments. Among these species, the Asian tiger mosquito, Aedes albopictus, is a threatening vector of several human viral diseases, including dengue and chikungunya, and raises concerns about the Zika fever. Its broad presence in both temperate and tropical environments has been considered the reflection of great "ecological plasticity." However, no study has been conducted to assess the role… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 87 publications
1
27
0
Order By: Relevance
“…Although invaders originating from cold environments were probably preadapted for invading temperate regions, some studies suggest the two other adaptation scenarios (genetic shift and bridgehead scenario) might still occur. The only other study investigating genomic signatures of selection in A. albopictus compared temperate invasive and tropical native populations (Goubert et al 2017). None of the potentially adaptive genes detected by the later study match those we detected within the native range, possibly because different genomic regions were targeted in the two studies (transposable elements insertion polymorphisms and ddRADseq SNPs).…”
Section: Invasionmentioning
confidence: 59%
See 3 more Smart Citations
“…Although invaders originating from cold environments were probably preadapted for invading temperate regions, some studies suggest the two other adaptation scenarios (genetic shift and bridgehead scenario) might still occur. The only other study investigating genomic signatures of selection in A. albopictus compared temperate invasive and tropical native populations (Goubert et al 2017). None of the potentially adaptive genes detected by the later study match those we detected within the native range, possibly because different genomic regions were targeted in the two studies (transposable elements insertion polymorphisms and ddRADseq SNPs).…”
Section: Invasionmentioning
confidence: 59%
“…The only other study investigating genomic signatures of selection in A. albopictus compared temperate invasive and tropical native populations (Goubert et al. ). None of the potentially adaptive genes detected by the later study match those we detected within the native range, possibly because different genomic regions were targeted in the two studies (transposable elements insertion polymorphisms and ddRADseq SNPs).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Invertebrate species are particularly strongly influenced by climatic conditions on many biological characters, such as reproduction, developmental durations, diapause and survival. Studies have shown differences in climatic adaptation between invasive and non‐invasive populations of invertebrates (Goubert et al, 2017; Hill, 2013; Jarošík, Kenis, Honěk, Skuhrovec, & Pyšek, 2015; Urbanski et al, 2012) and comparisons of species distributions in native and invaded regions provide additional indirect support for adaptive evolutionary shifts (Hoffmann, 2017). In newly colonized areas, climatic differences between early invaded areas and distribution edges may lead to differed selective pressures, and the opportunity to investigate rates of climatic adaptation in invading invertebrates.…”
Section: Introductionmentioning
confidence: 99%